Resilience of Potato Crop (Solanum tuberosum L.) to Hail Simulation at CIP Illpa - Luna Quecaño, Juan (2025)
Agricultural activity in recent decades has been affected by climate change, reducing harvests year after year; hail can damage crops depending on the size and intensity of the hail, potentially harming or even compromising the crop as a total loss. Understanding climate changes and the damage they cause in agriculture is essential for planning production systems, crop selection, seed variety, fertilizer application, among other actions. Once the potato crop is damaged by hail, it is important to know the resilience of the crop and take actions to continue or replace the crop. The objectives were to determine the resilience of the potato crop (Solanum tuberosum L.) against hail simulations at CIP Illpa; analyze the yields of the potato crop with different percentages of damage to the crop and analyze resilience in different phenological phases. The research methodology has a quantitative, experimental, descriptive, and sequential time approach, with an inferential non-parametric statistical design of completely randomized blocks (CRB) distributed in a factorial design of A3xB3xC2, where factor A represents the varieties; B represents the level of damage, and factor C the phenological phases. The results show that the Silver variety with simulated damage of 60% in the flowering phenological phase presents the greatest yield loss of the crop at 36.81%, and 27.24% in the Imilla negra variety. The interaction between the proposed factors does not show significance in its variables.